Single parenting in South African context : causes and effects on child welfare and development - Ahiaku, Philip; Ajani, Oluwatoyin Ayodele (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examined how single parenting in South Africa impact child welfare and development. Extant studies revealed that most African children are raised by single parents in diverse South African communities. African young adults both male and female were sampled to establish findings for this study. 150 single parents responded to the study’s survey questionnaire, while 15 single parents were engaged in semi-structured interviews. The instruments were descriptively and thematically analysed for questionnaire and interview respectively. Most of the single parents sampled struggle to provide for their children. It is also evident that for parenting, the physical and spiritual development of children are influenced by single parenthood. It is clear from the survey data that the socioeconomic status of single parents impact child education, feeding, housing and protection. It is suggested that adequate attention be paid to marriage among young youth by looking at the current cultural marriage rites which are crucial in building a sustainable and healthy family. Marriage allows partners to put available resources together to take care of children and this enhances the welfare and social development of the children.research significance in brief, research process, overall findings and conclusion or implications of the study.